Convergence in The Agricultural Economic Industry in Indonesia: A Dynamic - Fitriadi, Fitriadi; Junaidi, Agus; Darma, Dio Caisar (JSEP (Journal of Social and Agricultural Economics), 2024)
In addition to labor, investment, consumption, government spending, and exports, this work attempts to include elements of health, education, and technology which are seen as important in strengthening the agricultural sector. The paper aimed to assess the relationship between labor, investment, consumption, government spending, and exports on agricultural GDP based on two formats. First, modeling without health, education, and technology. Second, modeling includes health, education, and technology. A series of data series were observed in simultaneous and partial regression modeling. The case study is Indonesia, where testing was conducted during 2010–2022. The empirical findings conclude two points: (1) involving health, education, and technology, results are better on agricultural GDP growth than without including all three; and (2) although initially health, education, and technology were very essential, only health has positive implications for GDP growth. Without these three variables, in the short term, labor, investment, consumption, government spending, and exports also play a role in the development of the agricultural economy in Indonesia. Thus, labor, consumption, and exports remain to be increased for the future of agricultural GDP by optimizing human capital through health, education, and technology.